Transfusion-related acute lung injury in a COVID-19–positive convalescent plasma recipient: a case report. Issue 8 (August 2021) - Amrutiya, Viralkumar; Patel, Rutwik; Baghal, Moaaz; Patel, Bhoomi; Waykole, Trupti; Patel, Harshana; Govil, Swati; Lo, Abraham
We present a case of transfusion-related acute lung injury as a complication of convalescent plasma transfusion in a patient who presented with COVID-19–related severe acute respiratory syndrome. Despite treatment with tocilizumab, remdesivir, and intravenous steroids, worsening dyspnea prompted adjunctive treatment with convalescent plasma. Two hours after completion of the plasma transfusion, the patient developed hypoxia-induced cardiac arrest secondary to transfusion-related acute lung injury. This case sheds light on life-threatening transfusion reactions and emphasizes the need to investigate post-transfusion monitoring protocols as well as the possible role of surveillance equipment.